2017
DOI: 10.1515/jhsl-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

When natives became Africans: A historical sociolinguistic study of semantic change in colonial discourse

Abstract: The word native is a key term in nineteenth-century British colonial administrative vocabulary. The question is how it comes to be central to the classification of indigenous subjects in Britain’s southern African possessions in the early twentieth century, and how the word is appropriated by colonial citizens to designate the race of indigenous subjects. To answer the question, I construct a semasiological history of native as a word that has to do with the identification of a person with a place by birth, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies focused on lexical semantics have shown that a meaningful correlation exists between word usage and key sociolinguistic categories, such as geographical region (Geeraerts et al. 1994), demographics (Robinson 2010, 2011), ideology (Fitzmaurice 2017), stance (Sandow & Robinson 2018). In this research, we discover underlying macro‐patterns of thinking operating across different communities of speakers, which are manifested through entire concepts, not just individual words.…”
Section: Scope Of the Researchmentioning
confidence: 99%
“…Studies focused on lexical semantics have shown that a meaningful correlation exists between word usage and key sociolinguistic categories, such as geographical region (Geeraerts et al. 1994), demographics (Robinson 2010, 2011), ideology (Fitzmaurice 2017), stance (Sandow & Robinson 2018). In this research, we discover underlying macro‐patterns of thinking operating across different communities of speakers, which are manifested through entire concepts, not just individual words.…”
Section: Scope Of the Researchmentioning
confidence: 99%